Student-Centred Instruction in Science and Technology: a Model of Factors at Organizational and Individual Levels - Pejić Papak, Petra; Valenčič Zuljan, Milena; Zuljan, Darjo (Revija za elementarno izobraževanje, 2021)
To achieve the goals of modern science and technologyteaching, it is vital to organize student-centred instruction (SCI). Theorganization of SCI requires the teacher’s ability to organize cognitivelychallenging teaching in a stimulating environment. The fundamental purposeof the study was to determine whether the teacher’s organization of SCI wasrelated to factors at the school level (organizational context) and factors at theindividual level (individual context). We designed a model comprising foursets of factors. The results show a statistically significant correlation betweenSCI and all four sets of factors.
Keywords: student-centred instruction; science and technology; four-factor model; professional development; stimulating environment